Influencing factors of the approval of the Young Scientists Fund of National Natural Science Foundation of China: a case study of Shanghai Jiao Tong University School of Medicine - CHEN Lihong; WANG Yan; ZHOU Xiangtian; ZHENG Junke; YAN Xiaoxiang (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2024)
Objective·In view of the low funding rate of the Young Scientists Fund of National Natural Science Foundation of China in the medical field, this research conducted an in-depth investigation of the applicants in a medical school and quantitatively analyzed the influencing factors of project establishment, so as to provide reference for further improving the quality of project application and strengthening the training of young medical talents.Methods·A cross-sectional survey was used to select applicants from secondary schools of Shanghai Jiao Tong University School of Medicine and its 13 affiliated hospitals who had experience in applying for the fund from 2020 to 2022. Logistic stepwise regression model was applied to modeling and analysis by using the project application result as the dependent variable and the applicants' basic information and application status as independent variables.Results·The analysis results of 921 applicants showed that educational background (OR=1.86, 95%CI 1.14‒3.04), graduate university (OR=2.45, 95%CI 1.47‒4.08), sufficient preliminary work foundation (OR=4.22, 95%CI 2.44‒7.29), average impact factor of representative works (OR=1.10, 95%CI 1.04‒1.17), and total self-evaluation score of application documents (OR=1.06, 95%CI 1.04‒1.08) were the main influencing factors for project approval. The average impact factor and the highest impact factor of the approved representative works showed an increasing trend year by year. In addition, the influencing factors for the approval of young doctors and full-time researchers were different. The longer the graduation time of young doctors, the lower the approval rate.Conclusion·The funding rate of Young Scientists Fund is low, and the requirements for scientific research achievements are increasing year by year. Attention should be paid to early accumulation and improving the quality of application writing. Further measures should be taken to strengthen the early training of young medical talents, improve cultivation measures and consolidate research foundations.